FACTORS FOR THE FORMATION OF FINANCIAL SECURITY FOR THE DEVELOPMENT OF DOMESTIC ENTERPRISES ON THE BASIS OF INNOVATION - RUSHCHYSHYN, Mariia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Attention has been updated to the problems of forming financial support for the implementation of investment and innovation projects of enterprises, which aim to ensure their innovative development. Therefore, the purpose of the study is to identify the composition and analysis of the factors of the formation of financial support for the development of enterprises in Ukraine on an innovative basis. A typology of the factors of attracting financial support for investment and innovation goals was carried out in two directions: (1) internal resources and capabilities of economic entities, (2) external sources of accumulation of financial resources. Among the internal factors, the influence of such as the financial and economic condition, results and business activity of enterprises, availability of internal investment capital, innovative and technological activity of business entities, financial security and protection of intellectual property objects of innovatively active enterprises was analyzed. According to external factors, such as the development of the financial and credit system of the region, the activities of venture funds, business angels, the state of development of innovative infrastructure and the business environment were analyzed. The conditions that determine the specified factors of financial support for the innovative development of domestic enterprises are characterized, as well as their current state and the main problems that prevent the full involvement of financial and investment assets sufficient for the full-fledged conduct of innovative and technological activities by economic entities of Ukraine are identified. The scientific novelty of the research results lies in the further development of the methodological and applied principles of classification and typology of the factors of the formation of financial support for the activation of innovative activities of enterprises. The applied value of the research results lies in the possibility of identifying the available factors for the formation of financial and investment support for innovative and technological growth of business entities.